Kursus dan Pelatihan Bahasa Inggris pada Generasi Muda Dusun Upunyor Desa Weraru Kecamatan Moa Lakor Kabupaten Maluku Barat Daya - Romkeny, Hermelina; Lerrick, Meilisa Everdina; Sulimaly, Petronela; Porsiana, Sin Algonda; Imbama, Dorkas; Bastian, Barbalina Marta; Ratuhalano, Rita Marlin; Permaha, Yakoba; Keilaikou, Julio; Cinde, Nensia; Harmoko, Harmoko (UKInstitute, 2022)
Knowledge of English is one of the supports for the easy generation in facing the development of an increasingly advanced era. The purpose of implementing the English language course program is to provide knowledge of English to the younger generation in Upunyor Hamlet, Werwaru Village. The implementation of the English language course is carried out every week on Saturday afternoons for 2-3 hours of meetings. The trainees are the younger generation in Upunyor Hamlet. The results of the training showed that the implementation of the English language training carried out by KKN PSDKU UNPATTI students was running quite smoothly and there were no significant obstacles, this could be seen from the enthusiasm of the younger generations of Upunyor Hamlet in participating in the training from the beginning to the end of the meeting. From the results during the training, it was clear that the trainees understood and understood English quite well, which can be seen from the results of the practice of speaking English. Abstrak: Pengetahuan bahasa inggris menjadi salah satu penunjang para generasi mudah dalam menghadapi perkembangan zaman yang semakin maju. Tujuan pelaksanan program kurkus bahasa inggris yaitu untuk memberikan pengetahuan berbahasa inggris kepada generasi muda di Dusun Upunyor, Desa Werwaru. Pelaksanaan kursus bahasa inggris dilaksanakan setiap minggu di hari sabtu sore selama 2-3 jam pertemuan. Peserta pelatihan yaitu generasi mudah di Dusun Upunyor. Hasil pelatihan menunjukkan bahwa pelaksanaan pelatihan bahasa inggris yang dilaksanakan oleh mahasiswa KKN PSDKU UNPATTI terbilang berjalan cukup lancar dan tidak ada kendala berarti, hal tersebut dapat terlihat dari antusiasnya para generasi mudah Dusun Upunyor dalam mengikuti pelatihan dari awal hingga akhir pertemuan. Dari hasil selama pelaksanaan pelatihan terlihat jelas bahwa para peserta pelatihan cukup memahami dan mengerti berbahasa bahasa inggris yang dapat dilihat dari hasil praktek berbahasa inggris.